Novel super-hydrophobic PDRC coating with high mechanical strength and preparation method thereof
The new superhydrophobic PDRC coating prepared by a one-step spraying process uses silane coupling agent to modify polymers and SiO2/TiO2 particles to solve the problems of complex preparation and poor mechanical properties of existing coatings, and achieves efficient and durable radiation cooling effect.
Patent Information
- Application Number
- CN202411807844.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing superhydrophobic PDRC coatings are complex in the preparation process, difficult to produce on a large scale, and have weak mechanical properties, poor durability, and a large amount of energy is required for high-temperature sintering.
A novel superhydrophobic PDRC coating consisting of poly(glycidyl methacrylate-co-methacrylate) poly(GMA-co-FMA) and SiO2/TiO2 particles modified by a silane coupling agent-KH550 were prepared by a one-step spraying process.
It achieves high solar reflectivity, excellent mechanical durability and self-cleaning performance, can effectively prevent dust from adhesion, and maintain good optical performance at high temperatures, providing a net cooling power of 109.2W/m2.
Smart Images

Figure CN119799109A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PDRC coatings, and in particular to a novel super-hydrophobic PDRC coating with high mechanical strength. Background Art
[0002] Global warming and energy crisis are becoming increasingly serious. The widespread use of compressor refrigeration air conditioning systems has greatly increased greenhouse gas emissions and energy consumption. It is estimated that by 2040, the energy consumption of air conditioning may increase to 16 times the current level. Passive daytime radiative cooling (PDRC) is an emerging energy-free and environmentally friendly cooling technology that achieves cooling without external energy by reflecting sunlight (0.3-2.5μm) and emitting thermal radiation into space through the long infrared atmospheric window (8-13μm).
[0003] Unlike conventional air conditioning systems, PDRC does not require electricity, making it an attractive candidate for mitigating global warming and the energy crisis. However, as a building coating, PDRC coatings are susceptible to harsh atmospheric conditions, including dust pollution, wind erosion, and mechanical shock. If not cleaned or repaired in time, these factors may significantly reduce their cooling efficiency. Therefore, it is crucial to prepare radiative cooling coatings (such as superhydrophobic coatings) with self-cleaning properties. At present, there have been some advances in superhydrophobic PDRC coatings. For example, Mei et al. developed a double-layer radiative cooling coating with a solar reflectivity of 92%. The coating was modified by chemical vapor deposition and exhibited superhydrophobicity. Nie et al. reported a radiative cooling film prepared by a two-step knife coating method, which had a solar reflectivity of 85% and a superhydrophobicity of 162°. Although there have been some reports on superhydrophobic PDRC coatings, these coatings either have complex preparation processes that are not conducive to large-scale production, or have weak mechanical properties and poor durability. Recently, a superhydrophobic PDRC coating with excellent mechanical strength was prepared by sintering bauxite particles at 600°C. 21 However, the high-temperature sintering process requires a lot of energy. Therefore, it is still a huge challenge to prepare superhydrophobic PDRC coatings with mechanical strength using a simple and low-energy spraying process. Summary of the invention
[0004] In order to make up for the deficiencies of the prior art, the present invention provides a novel super-hydrophobic PDRC coating with high mechanical strength and a preparation method thereof.
[0005] The present invention is achieved through the following technical solutions:
[0006] In the first aspect, the present invention provides a novel super-hydrophobic PDRC coating with high mechanical strength, which is composed of poly(glycidyl methacrylate-co-3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate) poly(GMA-co-FMA) modified by a silane coupling agent-KH550 and SiO2 / TiO2 particles, and is prepared by a one-step spraying process; the coating achieves a high solar reflectivity of 91.06% and a mid-infrared emissivity of 93.72%, and has a super-hydrophobicity of 157°, which can effectively prevent dust adhesion; the coating maintains excellent durability and optical properties after 3000 wear cycles with a load of 250g; at 780W / m 2 Under the solar radiation intensity of 109.2W / m 2 Net cooling power.
[0007] In a second aspect, the present invention provides a method for preparing a novel super-hydrophobic PDRC coating with high mechanical strength, comprising the following steps:
[0008] (1) Synthesis of poly(GMA-co-FMA)
[0009] Poly(GMA-co-FMA) was synthesized by thermally initiated free radical polymerization; glycidyl methacrylate-GMA and 3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate-FMA in molar ratios of 1:1, 1:2, 1:3, and 1:4 were dissolved in butyl acetate and stirred for 15-45 min; then azobisisobutyronitrile-AIBN was added as a thermal initiator, the solution was degassed by purging with N2, and then stirred at 70°C for 10-12 h;
[0010] (2) Preparation of Passive Daytime Radiative Cooling (PDRC) Coating
[0011] SiO2 and TiO2 nanoparticles in different mass ratios are dispersed into the poly (GMA-co-FMA) solution and stirred at room temperature for 2-3 hours; while stirring continuously, KH-550 of equal mass to GMA is gradually added to the suspension; a spray gun with a 2.5mm nozzle is used at a distance of 15-35cm from the substrate to spray the substrate surface at an air pressure of 0.4-0.6MPa for 15-25s; after spraying, the coated substrate is dried at room temperature for 12-24h.
[0012] Preferably, in step (1), the mass of azobisisobutyronitrile-AIBN is relative to the total mass of GMA and FMA.
[0013] Preferably, in step (1), glycidyl methacrylate - GMA and 3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate - FMA are dissolved in butyl acetate, stirred for 15 minutes, the solution is degassed by purging with N2, and stirring is continued at 70°C for 12 hours.
[0014] Preferably, in step (2), the mass ratio of SiO2 and TiO2 nanoparticles is any one of 1:0, 3:1, 1:1, 1:3, and 0:1.
[0015] Preferably, in step (2), SiO2 and TiO2 nanoparticles in different mass ratios are dispersed into a poly(GMA-co-FMA) solution and stirred at room temperature for 3 h; while stirring continuously, KH-550 is gradually added to the suspension; a spray gun with a 2.5 mm nozzle is used at a distance of 20 cm from the substrate; after spraying, the coated substrate is dried at room temperature for 12 hours
[0016] In a third aspect, the present invention provides applications of novel superhydrophobic PDRC coatings in net radiative cooling, including building cooling and energy management.
[0017] In a fourth aspect, the present invention provides the use of a novel super-hydrophobic PDRC coating in the preparation of a self-cleaning product.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] The present invention develops a new super-hydrophobic PDRC coating with high mechanical strength, which can be prepared by a large-scale production and low-energy spraying process. The PDRC coating is composed of poly(glycidyl methacrylate-co-3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate) (poly(GMA-co-FMA)) modified by a silane coupling agent (KH550) and SiO2 / TiO2 particles. By adjusting the mass ratio of SiO2 and TiO2 and the content of poly(GMA-co-FMA), the optimized PDRC coating exhibits a solar reflectivity of 91.06% and an emissivity of 93.72%, and has a super-hydrophobicity of about 157°, which effectively prevents dust adhesion. In addition, the PDRC coating still maintains a reflectivity of 91.06% after 3000 wear cycles with a load of 250 grams, indicating that it has excellent mechanical durability. The excellent optical properties make the coating surface temperature drop by about 13.2℃, providing about 109.2W / m 2 The PDRC coating can be further processed into different color variants without affecting its high reflectivity and emissivity, making it suitable for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention will be further described below in conjunction with the accompanying drawings.
[0021] Figure 1 Schematic diagram of the manufacturing process and functional characteristics of the PDRC coating structure of the present invention;
[0022] Figure 2 It is the synthetic molecular formula of acrylic acid polymer;
[0023] Figure 3 The adhesion strength and contact angle of coatings made with different monomer ratios;
[0024] Figure 4 (a) Schematic diagram of infrared radiation caused by the molecular structure and functional groups of GMA and FMA. (b) Infrared absorption peak of poly(GMA-co-FMA). (c) SEM image and elemental mapping of C, O, F, Si and Ti, (d) Long infrared emissivity curve of the coating;
[0025] Figure 5 (a) Full range XPS spectrum (b) C 1s, (b) O 1s and (d) F 1s spectra.
[0026] Figure 6 (a) Comparison of scattering behavior of a single particle and two types of particles; Scattering efficiency of SiO2 (b) and TiO2 particles (c) as a function of particle size, wavelength range 0.3 to 2.5 μm; (d) Reflection spectra of coatings at different particle mass ratios; (e) Reflection spectra of coatings with different particle contents; (f) Photograph of PDRC coating (50 cm x 50 cm) and SEM cross-sectional image of coating (inset); (g) Photograph of silver mirror phenomenon and contact angle (inset); (h) Photograph of spherical droplets of water, dyed water (blue), tea, and cola on the coating. (i) Photograph of water droplets bouncing off the coating;
[0027] Figure 7 SEM images of coatings with different SiO2 and TiO2 mass ratios;
[0028] Figure 8 Contact angles of coatings with different SiO2 and TiO2 mass ratios;
[0029] Fig. 9 For pictures of cleaning sand from the coating;
[0030] Fig.10(a) Photos of PDRC coatings on different substrates; (b) Adhesion strength of PDRC coatings on different substrates; (c) Photos of 3M grid test; (d) Schematic diagram of tape stripping process; (e) Contact angle and sliding angle of PDRC coating after tape stripping test; (f) Taber abrasion machine wear test and photos of samples before (top) and after (bottom) test; Reflectivity curves of PDRC coatings after Taber wear test (g), chemical corrosion (h) and UV irradiation (i), respectively; (j) Photos of PDRC coatings of different colors; (k) Optical properties of colored PDRC coatings;
[0031] Fig.11 Rating of coating test results (GB / T 9286-2021);
[0032] Fig.12 Photo (a) and schematic diagram (b) of the temperature measurement equipment; (c) solar irradiance measured in the experiment; (d) temperature of bare glass and PDRC-coated glass under solar intensity; (e) average temperature difference in d; (f) photo of the tank device in the outdoor environment and schematic diagram of the temperature measurement area in the tank; (g) real-time temperature curves of air and water in the tank; (hj) calculated radiative cooling power (P) at different relative humidity (RH) net );
[0033] Fig.13 3D printed oil tank model. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the accompanying drawings.
[0035] Example 1
[0036] Material
[0037] Glycidyl methacrylate (GMA, 97%), 3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate (FMA, 98%), (3-aminopropyl)triethoxysilane (KH-550, 99%), azobisisobutyronitrile (AIBN), SiO2 nanoparticles (500 nm), butyl acetate, HCl, NaOH, and NaCl were purchased from Shanghai MacLean Biochemical Co., Ltd. (China). Titanium dioxide (TiO2, 100 nm, rutile phase) was purchased from Aladdin Reagent Co., Ltd. (China).
[0038] Synthesis of poly(GMA-co-FMA)
[0039] Poly(GMA-co-FMA) was synthesized via thermally initiated free radical polymerization.
[0040] GMA and FMA in a molar ratio of 1:2 were dissolved in butyl acetate and stirred for 15 minutes. AIBN (1 wt%, relative to the total mass of GMA and FMA) was then added as a thermal initiator. The solution was degassed by purging with N2 and then stirred continuously at 70°C for 12 hours.
[0041] Preparation of Passive Daytime Radiative Cooling (PDRC) Coatings
[0042] SiO2 and TiO2 nanoparticles in different mass ratios (1:0, 3:1, 1:1, 1:3, 0:1) were dispersed into poly(GMA-co-FMA) solution and stirred at room temperature for 3 h. KH-550 was gradually added to the suspension while stirring continuously. A spray gun with a 2.5 mm nozzle was used at a distance of 20 cm from the substrate. After spraying, the coated substrate was dried at room temperature for 12 h.
[0043] Example 2
[0044] Structural characterization
[0045] The surface morphology of the coatings was examined using a scanning electron microscope (SEM, Hitachi Regulus 8220). The elemental composition of the coatings was analyzed by energy dispersive spectroscopy (EDS, EDAX Octane), while the functional groups were identified using Fourier transform infrared spectroscopy (FTIR, TENSOR) and X-ray photoelectron spectroscopy (XPS, ESCALAB+).
[0046] Optical performance characterization
[0047] The solar reflectance spectra (0.3-2.5 μm) of the coatings were measured using a UV-Vis-NIR spectrophotometer (TP-100) equipped with a BaSO4 integrating sphere. The mid-infrared emissivity spectra (2.5-20 μm) were measured using a FTIR spectrometer (Nicolet TM iS50) was obtained.
[0048] Average solar reflectivity and the average mid-wave infrared emissivity Using formulas (1) and (2) respectively 1 calculate:
[0049]
[0050] Here, λ represents wavelength, AM 1.5 is the solar spectral intensity at wavelength, R(λ) is the spectral reflectance of the sample, ε(λ) is the spectral emissivity, I BB (λ,T) is the blackbody spectral radiation intensity at temperature T.
[0051] Calculation of radiative cooling performance
[0052] The net cooling power of the radiant cooler can be expressed as 2 :
[0053] P net (T) = P rad (T)-P sun -P atm (T amb )-P cond+conv (T,T amb ) (3)
[0054] where:
[0055] ·P rad (T) is the radiant power of the cooler,
[0056] ·P sun represents the absorbed incident solar energy,
[0057] ·P atm (T amb ) is the atmospheric transmission radiation absorption power,
[0058] ·P cond+conv (T,T amb ) considers the power absorbed by convection and conduction heat transfer processes.
[0059] Radiated power P rad (T) can be determined using the following integral:
[0060]
[0061] Here I B (T),λ) is the spectral radiance of a black body at temperature T, described by Planck's law:
[0062]
[0063] In this equation, h represents Planck's constant, k B is the Boltzmann constant, c is the speed of light, and λ is the wavelength.
[0064] The solar power absorbed by the cooler is given by:
[0065]
[0066] Among them I AM1.5 (λ) is the spectral irradiance under standard solar conditions.
[0067] Atmospheric transmission radiation absorption can be expressed as:
[0068]
[0069] In this case, T amb represents the ambient temperature, ε atm (λ,θ) is the spectral emissivity of the atmosphere, and ε(λ,θ) represents the spectral absorptivity of the radiative cooling material. The emissivity can be used to derive Kirchhoff's law of thermal radiation, which is defined as:
[0070]
[0071] where t(λ) is the transmittance of the atmosphere.
[0072] The power absorbed by convection and conduction processes is calculated as follows:
[0073] P cond+conv (T,T amb )=A·h c ·(T amb -T) (9)
[0074] where h c is the convective heat transfer coefficient and A is the surface area of the test sample involved in radiative cooling.
[0075] In this study, it is assumed that the sunlight hits the sample vertically, that is, the incident angle is zero degrees (θ o =0). This assumption greatly simplifies the formula, eliminates the need for angles, and makes the calculation more intuitive.
[0076] Wetting properties
[0077] The contact angle and sliding angle of the coating were measured using a KRüSS DSA25S (KRüSS, Germany). To measure the contact angle, a drop of water (~4 μL) was placed on the sample surface by squeezing a syringe, and the contact angle of the sample was obtained by side-view photography after the droplet stabilized. To measure the sliding angle, the test platform was initially tilted at an angle of 0o, and a drop of water (~4 μL) was placed on the sample surface by squeezing a syringe. The tilt angle was controlled by adjusting the rotation button of the platform. The rotation was stopped when the drop began to roll on the surface, and the corresponding angle was recorded as the sliding angle. Each sample was measured at three different positions to minimize data errors.
[0078] Adhesion test
[0079] To evaluate the adhesion of the coating on various substrates, tests were conducted using an adhesion tester and mechanical adhesion methods in accordance with GB / T 5210-2006. The spindle was bonded to the coating surface using a special adhesive compatible with the test instrument and then cured at room temperature for 72 hours. A cutter was then used to carefully cut around the spindle. Subsequently, the safety valve of the test instrument was turned counterclockwise to completely loosen it, allowing the sleeve to connect to the spindle. The test involves a "peak measurement" in which the system is pressurized until the coating adheres to the spindle separated from the substrate. The peak pressure recorded at this time is used to quantify the bond strength between the coating and the substrate.
[0080] Scratch Adhesion Test
[0081] Adhesion test is carried out according to the standard test method (GB / T 9286-2021). Using a cross-cut tester, the blade is perpendicular to the sample surface and cuts a 1mm x 1mm 10x10 grid on the coating surface at a constant speed. Subsequently, a brush is used to remove debris in the test area.
[0082] Tape peel test
[0083] The tape peeling test was carried out using the standard test method. The 3M tape was attached to the coating surface, pressed down with a 500g roller, the roller was rolled up to compress the tape, and then quickly peeled off. The contact angle and sliding angle of the coating were recorded every 10 times.
[0084] Taber Wear Test
[0085] The abrasion resistance of the coating was evaluated using a TaberAbrader (USA Model 1700) according to ASTM D4060. Two 250 g loads were applied. For a CS-10 grinding wheel, each 360° rotation is considered as one cycle. The coating on a glass substrate with a diameter of 10 cm was tested for 3000 abrasion cycles. The abrasion resistance was evaluated by comparing the solar reflectance of the coating before and after the abrasion test.
[0086] Corrosion resistance test
[0087] The corrosion resistance was evaluated by immersing the coating (on a glass substrate) in aqueous solutions with different pH values. The coating was immersed in these solutions for one month. After immersion, the coating was dried in an oven at 45°C for 1 hour. The corrosion resistance was evaluated by comparing the solar reflectance before and after immersion.
[0088] Anti-ultraviolet aging test
[0089] The UV-LED oven (UVLED-OS, China) was used to evaluate the UV aging resistance of the coating, which simulates the short and medium wavelength range of the sunlight UV spectrum at a peak wavelength of 365nm. The coating was exposed to UV radiation for 264 hours (~10 days) in the center of the chamber. The UV aging resistance was determined by measuring the solar reflectivity of the coating before and after UV exposure.
[0090] Example 3
[0091] To prepare the PDRC coating, GMA and FMA were polymerized at different molar ratios (see Figure 2 ). By comparing the adhesion to the substrate and the surface hydrophobicity, GMA and FMA with a molar ratio of 1:2 were selected for free radical polymerization (see Figure 3 Subsequently, SiO2, TiO2 and KH-550 were added to the polymer solution and processed by a simple spraying process (see Figure 1 ). The PDRC coating exhibits excellent radiative cooling properties and superhydrophobicity due to its low surface energy and micro-nanostructural features. These properties enable surface contaminants to be easily removed by precipitation, thereby maintaining long-term optical properties. In addition, the -NH3 groups in KH-550 can react with the epoxy groups in the polymer, while the Si-OC groups are easily hydrolyzed, significantly enhancing the intrinsic strength of the coating and its adhesion to the substrate.
[0092] Poly(GMA-co-FMA) is a long-chain acrylic polymer that exhibits strong infrared radiation characteristics within the atmospheric window. Figure 4 a shows the molecular structures of two acrylic monomers, GMA has C=O and COO groups, while FMA has CF bonds. The unique vibration modes and frequencies of these chemical bonds enhance the radiation performance of the polymer, especially within the atmospheric window, thereby improving its infrared radiation characteristics. Figure 4 b It can be seen that the absorption peak at 1730cm-1 corresponds to the stretching vibration of C=O, the absorption peak at 1236cm-1 corresponds to the symmetric stretching vibration of -COC in the ester group, and the peak at 1300cm-1 is attributed to the stretching vibration of the CF bond. In addition, the peak at 930cm-1 corresponds to the vibration of the epoxy group. These absorption peaks are highly consistent with the frequency range of the atmospheric transparency window, thus helping to enhance the infrared radiation performance, thereby showing excellent PDRC performance. In addition, the FTIR spectrum does not show a C=C absorption peak, and the C 1s XPS spectrum does not detect any C=C bonds (see Figure 5 ), which confirmed the successful polymerization of the monomer. Figure 4 As can be seen in Fig. c, the microstructure of the coating and the uniform distribution of elements, especially the high concentration of fluorine on the surface, are crucial for superhydrophobicity and high emissivity. Figure 4As shown in Figure d, the average emissivity in the range of 8–13 μm is 93.72%, demonstrating excellent infrared radiation performance within the atmospheric window, emphasizing the potential of this polymer in radiative cooling applications.
[0093] Ideally, a radiative cooling coating should have a strong ability to scatter sunlight. Figure 6 a shows the scattering mechanism of the coating on the incident light. According to Snell's law, the greater the difference in refractive index (n) between the two media, the greater the angle of refraction of the light. SiO2 was chosen for its availability and cost-effectiveness. However, a single SiO2 layer has a smaller refractive index difference between SiO2 (n = 1.5) and air (n = 1) ( Figure 6 a top schematic diagram), resulting in limited solar reflectivity and insufficient backscattering. To enhance scattering, TiO2 ( Figure 6 a (bottom schematic diagram). This dual-particle system is able to reduce the incident light entering the substrate, thereby achieving effective scattering. In addition, particles with a specific size will scatter the incident light in different wavelength ranges according to the Mie scattering theory. Here, the scattering intensity of SiO2 and TiO2 nanoparticles of different sizes in the solar spectrum is calculated ( Figure 6 bc). In order to maximize the scattering efficiency in the visible spectrum, 500nm SiO2 particles and 100nm TiO2 particles were selected, as these particle sizes have been shown to scatter sunlight best in this wavelength range. After determining the optimal particle size, the effect of different mass ratios of SiO2 and TiO2 on the coating performance was studied. Figure 6 As shown in Figure d, the reflectivity of the coating with a SiO2 to TiO2 mass ratio of 3:1 is about 4.9% higher than that of the coating composed of SiO2 particles alone. However, further increasing the proportion of TiO2 leads to a gradual decrease in reflectivity, which may be due to the fact that the microstructure of the coating is too dense and small TiO2 particles accumulate on the SiO2 surface, limiting the scattering of light (see Figure 7 ). The surface structure of the coating not only affects the reflectivity of sunlight, but also the wettability of the coating surface. The contact angles of the coatings with different mass ratios are as follows: Figure 8 As shown. Based on the optimal balance between reflectivity and hydrophobicity, a coating with a mass ratio of SiO2 to TiO2 of 3:1 was selected. Under this ratio, when the particle content reached 40wt%, the reflectivity of the coating reached 91.06% (see Figure 6 e).
[0094] Figure 6f shows a representative uniform white coating prepared by a simple spraying process, indicating that our coating can be easily mass-produced. The thickness of the coating was confirmed by a scanning electron microscopy (SEM) image of the cross section, which is only 97.5 μm. This thickness is thinner than the coatings reported in other studies, which will significantly reduce production costs and expand practical applications. The PDRC coating has excellent self-cleaning ability (see Fig. 9 When the coating is immersed in water, a large number of tiny bubbles are attached to the surface, giving it a mirror-like luster (see Figure 6 f). The contact angle of the coating was observed to be as high as 157° (see Figure 6 f illustration). Figure 6 h shows the superhydrophobic behavior of the coating to various liquids (such as water, dyed water, tea, and cola), all of which form obvious spherical water droplets on the coating surface, indicating its excellent liquid repellency. Figure 6 As shown in Figure 1, the water droplet bounced off the coating completely without leaving any residual trace after contact with it, demonstrating the excellent liquid repellency of the coating. These results indicate that the coating has excellent self-cleaning ability and can prevent dirt and liquid adhesion, thereby enhancing long-term durability.
[0095] The mechanical strength of the coating is a key factor in evaluating its outdoor performance. The PDRC coating can be applied to different substrates (see Fig.10 a). The study found that the tensile peel strength of the coating on different substrates ranged from 0.91 to 1.41 MPa (see Fig.10 b), fully meeting the requirements of coatings in different occasions. In addition, through the scratch test, the actual damage of the marked area is less than or equal to 5% (see Fig.10 c), indicating that the coating has reached the first-class standard (see Fig.11 ). Use a 500g roller to apply pressure to the 3M tape on the PDRC coating to enhance adhesion (see Fig.10 d). After 30 cycles of pressing and peeling, the contact angle decreased slightly and the sliding angle was still less than 10° (see Fig.10 e), indicating that the coating has good self-cleaning ability. To evaluate the mechanical properties, a cyclic friction test was performed using a Taber abrasion machine and a load of 250 g was applied during clockwise cyclic friction (see Fig.10 f). After 3000 abrasion cycles, the reflectivity of the coating did not change significantly (see Fig.10 g). In addition, the coating exhibits excellent chemical stability. After being immersed in different acidic and alkaline solutions for one month (pH = 1, 7 and 14), the reflectivity did not change significantly (see Fig.10 h). To evaluate the weathering resistance, the coatings were exposed to 365 nm UV light for a total of 264 hours, during which time the reflectivity showed little change (see Fig.10 i).
[0096] In order to expand the application of coatings, PDRC coatings of different colors have been prepared. Fig.10 As shown in Figure 5, PDRC coatings in bright colors such as yellow, pink, blue, and green were prepared by simply mixing color pigments with the spray suspension. By comparing the optical properties of the colored coatings and the white coatings, it was found that the colored coatings maintained high reflectivity in different wavelength ranges, while the emissivity in the range of 8-13μm remained almost unchanged. These versatile optical properties not only enhance the potential of the coatings in radiative cooling applications, but also expand their flexibility in aesthetics and design. Overall, these results indicate that the coatings are highly efficient in radiative cooling and exhibit excellent durability.
[0097] In order to verify the actual radiative cooling performance of the coating, an outdoor experiment was conducted on the roof of Qilu University of Technology (latitude N6.55°, longitude E 116.75°, Jinan, Shandong) on August 11, 2024. Fig.12 As shown in ab, a self-constructed experimental setup was designed, which consists of a polyethylene (PE) foam box wrapped with aluminum foil (Al). The aluminum foil can reflect the radiation from surrounding objects and reduce the influence of external interference on the experimental results. The sample was placed in the foam box, and a K-type thermocouple was placed under the sample for accurate temperature measurement. In order to minimize convection and heat transfer between the cavity and the external environment, the top of the foam box was sealed with PE film to create an ideal test environment. During the test, the solar radiation intensity (I solar ) reaches a peak of 780W m-2 at noon (see Fig.12 c). The real-time temperature curves of coated glass and bare glass show that the average temperature of coated glass is reduced by 7.8°C, with the maximum temperature difference being 13.2°C (see Fig.12 de).
[0098] In order to further verify the radiation cooling effect, a temperature measurement device was designed using a water tank model (see Fig.12 f and Fig.13 ). Two identical water tanks were prepared: one coated with PDRC and the other uncoated as a control. Both tanks were partially filled with water, and each was equipped with two K-type thermocouples, one placed in the air region above the water surface and the other immersed in the water. This setup allowed for continuous monitoring of the temperature in both regions. Fig.12 As shown in g, the real-time temperature curves of the PDRC-coated water tank and the bare water tank show obvious differences. PDRC-air ) and water (T PDRC-water ) were 42℃ and 43℃, which were significantly lower than the air in the bare water tank (T Bare-air ) and water (T Bare-water) temperature. Bare-air In comparison, T PDRC-air The maximum temperature decreased by 7.2℃, which is consistent with T Bare-water In comparison, T PDRC-water The maximum temperature reduction was 8°C. The PDRC coated tank remained consistently cooler than the bare tank in both the air and water zones, highlighting the practical benefits of the PDRC coating. The setup demonstrated the effectiveness of the coating in passive cooling, reducing heat within the tank and stabilizing the internal temperature. This configuration is highly valuable in applications that require thermal regulation without the use of active cooling, demonstrating the potential of the coating in energy-efficient temperature control solutions.
[0099] In order to quantitatively evaluate the radiative cooling performance of the PDRC coating, MATLAB simulation was used to calculate the theoretical net cooling power (P net (T)). The solar radiation intensity is fixed at 1000W m -2 , ambient temperature (T amb )) is 300K. Convective heat transfer coefficient (h c ) is defined as 3, 5, 7 and 9 W m -2 K -1 .P net (T) can be expressed as:
[0100] P net (T) = P rad (T)-P sun -P atm (T amb )-A·h c ·(T amb -T)
[0101] Among them, P rad (T) is the radiation power of the coating, P sun is the absorbed solar radiation power, P atm (T amb ) is the atmospheric transmission radiation absorption power, and A is the surface area of the test sample involved in radiation cooling. The specific parameter calculation can be found in the Supporting Information.
[0102] like Fig.12 hi shown, under dry conditions (RH = 0%, see Figure 5 ), the coating exhibited a maximum P net (T) is 109.2Wm -2 According to P net The cooling temperature determined by the zero intercept of (T) shows that at h c =3Wm -2 K -1The temperature reduction can reach 21.8°C when the temperature is reduced. This high cooling performance highlights the efficiency of the coating in arid climates dominated by radiative heat dissipation. Fig.12 i), P net (T) down to 95.5Wm -2 , the cooling temperature is about 19.2°C. Under high humidity conditions (RH = 30-50%, see Figure 5 ), P net (T) further decreased to 68.2Wm -2 , the cooling temperature dropped to 13.6°C. This significant drop can be attributed to the enhanced thermal radiation feedback of water vapor, which reduces the radiative heat exchange between the coating and the atmosphere. Despite these challenging conditions, the coating still exhibits significant cooling capacity and maintains its potential as an effective passive cooling solution.
[0103] In the present invention, a highly efficient, durable and self-cleaning radiative cooling coating was successfully developed, which was prepared by spraying a suspension of fluorinated acrylic polymer and SiO2 / TiO2 particles. The chemical bond vibration of the polymer contributes to its excellent infrared emissivity (93.72%). By optimizing the size and ratio of the nanoparticles, the best combination is 500nm SiO2 particles and 100nm TiO2 particles, with a ratio of 3:1 and a particle filling mass fraction of 40%. The resulting PDRC coating has a high reflectivity of 91.06% and a coating thickness of 97.5μm, showing excellent mechanical stability, self-cleaning properties, and long-term radiation resistance and anti-aging properties. The coating demonstrated impressive radiative cooling capabilities, with a maximum temperature reduction of 13.2℃ during the day and a net radiative cooling power of 109.2W m-2 achieved under dry conditions. This cost-effective and high-performance coating provides a viable solution for building cooling and energy management, enabling sustainable passive cooling.
Claims
1. A novel super-hydrophobic PDRC coating with high mechanical strength, characterized in that: The coating is composed of poly(glycidyl methacrylate-co-3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate) poly(GMA-co-FMA) modified by silane coupling agent-KH550 and SiO2 / TiO2 particles, and is prepared by a one-step spraying process; the coating achieves a high solar reflectivity of 91.06% and a mid-infrared emissivity of 93.72%, and has a super hydrophobicity of 157°, which can effectively prevent dust adhesion; The coating maintained excellent durability and optical properties after 3000 abrasion cycles at a load of 250g; 2 Under the solar radiation intensity of 109.2W / m 2 Net cooling power.
2. A method for preparing a novel super-hydrophobic PDRC coating with high mechanical strength according to claim 1, characterized in that: The following steps are involved: (1) Synthesis of poly(GMA-co-FMA) Poly(GMA-co-FMA) was synthesized by thermally initiated free radical polymerization; glycidyl methacrylate-GMA and 3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate-FMA in molar ratios of 1:1, 1:2, 1:3, and 1:4 were dissolved in butyl acetate and stirred for 15-45 min; then azobisisobutyronitrile-AIBN was added as a thermal initiator, the solution was degassed by purging with N2, and then stirred at 70°C for 10-12 h; (2) Preparation of Passive Daytime Radiative Cooling (PDRC) Coating SiO2 and TiO2 nanoparticles in different mass ratios are dispersed into the poly (GMA-co-FMA) solution and stirred at room temperature for 2-3 hours; while stirring continuously, KH-550 of equal mass to GMA is gradually added to the suspension; a spray gun with a 2.5mm nozzle is used at a distance of 15-35cm from the substrate to spray the substrate surface at an air pressure of 0.4-0.6MPa for 15-25s; after spraying, the coated substrate is dried at room temperature for 12-24h.
3. The method according to claim 2, characterized in that In step (1), the mass of azobisisobutyronitrile-AIBN is relative to the total mass of GMA and FMA.
4. The method according to claim 2, characterized in that: In step (1), glycidyl methacrylate (GMA) and 3,3,4,4,5,5,6,6,6-nonafluorohexyl methacrylate (FMA) were dissolved in butyl acetate and stirred for 15 minutes. The solution was degassed by purging with N2 and stirred at 70°C for 12 hours.
5. The method according to claim 2, wherein in step (2), SiO2 and TiO2 nanoparticles in different mass ratios are dispersed into a poly(GMA-co-FMA) solution and stirred at room temperature for 3 hours; while continuously stirring, KH-550 is gradually added to the suspension; a spray gun with a 2.5 mm nozzle is used at a distance of 20 cm from the substrate; after spraying, the coated substrate is dried at room temperature for 12 hours.
6. The method according to claim 2, characterized in that In step (2), the mass ratio of SiO2 and TiO2 nanoparticles is any one of 1:0, 3:1, 1:1, 1:3, and 0:
1.
7. A use of the novel superhydrophobic PDRC coating of claim 1 in net radiative cooling, including building cooling and energy management.
8. Use of the novel super-hydrophobic PDRC coating according to claim 1 in preparing a self-cleaning product.
Citation Information
Cited By
Double-layer super-hydrophobic passive daytime radiation cooling coating and application thereof
CN120737725A
Radiation refrigeration coating with recoverable function and preparation method thereof
CN121271428A